Adaptive divergence generates distinct plastic responses in two closely related Senecio species. (1st June 2022) - Walter, Greg M.; Clark, James; Cristaudo, Antonia; Terranova, Delia; Nevado, Bruno; Catara, Stefania; Paunov, Momchil; Velikova, Violeta; Filatov, Dmitry; Cozzolino, Salvatore; Hiscock, Simon J.; Bridle, Jon R.
Abstract: The evolution of plastic responses to external cues allows species to maintain fitness in response to the environmental variations they regularly experience. However, it remains unclear how plasticity evolves during adaptation. To test whether distinct patterns of plasticity are associated with adaptive divergence, we quantified plasticity for two closely related but ecologically divergent Sicilian daisy species ( Senecio, Asteraceae). We sampled 40 representative genotypes of each species from their native range on Mt. Etna and then reciprocally transplanted multiple clones of each genotype into four field sites along an elevational gradient that included the native elevational range of each species, and two intermediate elevations. At each elevation, we quantified survival and measured leaf traits that included investment (specific leaf area), morphology, chlorophyll fluorescence, pigment content, and gene expression. Traits and differentially expressed genes that changed with elevation in one species often showed little changes in the other species, or changed in the opposite direction. As evidence of adaptive divergence, both species performed better at their native site and better than the species from the other habitat. Adaptive divergence is, therefore, associated with the evolution of distinct plastic responses to environmental variation, despite these two species sharing a recent common ancestor.